2013
DOI: 10.1017/s1368980013002413
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition in older adults on financial assistance in an urban Asian country: a mixed methods study

Abstract: Objective: The objectives of the present study were to assess the nutritional status, identify factors for malnutrition risk and evaluate barriers to adequate nutrition among recipients of the Public Assistance (PA) scheme for socio-economically disadvantaged Singaporeans. Design: Using a cross-sectional study design, we assessed PA recipients' malnutrition risk using the DETERMINE Nutritional Health checklist and the full Mini-Nutritional Assessment (MNA), as well as their nutritional knowledge, co-morbidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 22 publications
(37 reference statements)
1
19
0
Order By: Relevance
“…Not surprisingly, our values were similar to the findings of several other studies (13,20,30) using the same assessment tool (MNA), cut-off score (≤23.5 points), and research subjects (community-dwelling elderly adults). Specifically, the incidence of malnutrition and RM in our study were similar to findings from Shanghai (1.7% and 19.1%, respectively), Guangzhou (1.0% and 29.2%, respectively), and Beijing (0.2% and 32.3%, respectively) in China, as well as in Japan (0.2% and 20.6%, respectively) and Singapore (2.8% and 50.3%, respectively) [6,14,16,17,31]. Conversely, a study by Han and colleagues in Wuhan,…”
Section: Comparison With Previous Studiessupporting
confidence: 88%
See 2 more Smart Citations
“…Not surprisingly, our values were similar to the findings of several other studies (13,20,30) using the same assessment tool (MNA), cut-off score (≤23.5 points), and research subjects (community-dwelling elderly adults). Specifically, the incidence of malnutrition and RM in our study were similar to findings from Shanghai (1.7% and 19.1%, respectively), Guangzhou (1.0% and 29.2%, respectively), and Beijing (0.2% and 32.3%, respectively) in China, as well as in Japan (0.2% and 20.6%, respectively) and Singapore (2.8% and 50.3%, respectively) [6,14,16,17,31]. Conversely, a study by Han and colleagues in Wuhan,…”
Section: Comparison With Previous Studiessupporting
confidence: 88%
“…Meanwhile, mixed findings have been reported regarding the prevalence of malnutrition and the risk of malnutrition (RM). Based on the Mini Nutritional Assessment (MNA) scale, the incidence of malnutrition in community-dwelling elderly adults varies between 0.2% and 13.7%, as well as 8% to 50.3% of elderly individuals have RM (10,(13)(14)(15)(16)(17)(18). Differences in sample size, age distribution, diversified social environment, and geographical differences may all contribute to the variations between studies (14).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the present meta-analysis also established an association between lowest income levels and a higher risk of developing malnutrition in the elderly. One explanation is based on the fact that the healthiest or freshest food is the most expensive, so are not accessible for the elderly with few economic resources [64]. Thus, all of these low income-associated aspects could increase the risk of malnutrition and could be a determinant of malnutrition in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…An individual's competency in obtaining, understanding nutrition information, and knowing how to access nutrition health services have an impact on the nutrition knowledge of the individual. Studies have reported that the lack of aforementioned skills may contribute to poor nutrition health (10,18). Nutrition attitudes is centered on the perceptions and beliefs influencing food choices (13,14), mediating the link between nutrition knowledge and dietary habits (19).…”
Section: Introductionmentioning
confidence: 99%